Madness in the Organic Order of Space. Kant and the Imagination - Costantini, Marco (Con-Textos Kantianos. International Journal of Philosophy, 2021)
In this paper, I first examine the classification of mental derangements contained in Kant’s Anthropology from a Pragmatic Point of View, in order to highlight the role played by imagination in their pathogenesis. Later, on the basis of this examination, I reflect on the origins of critical philosophy, which can be seen as an attempt to construct a control device for the imagination structured as a systematic, organic space.